ANALYSIS OF THE DECISION ON THE CASE OF WALI ADHAL IN THE MARRIAGE OF A GIRL IN THE BOGOR RELIGIOUS COURT - Rossa, Annisa Destiana; Sutisna, Sutisna; Hambari, Hambari (IBN KHALDUN BOGOR, 2024)
Marriage is a sacred thing in carrying out worship to Allah, by entering into marriage, every thing that is done will produce extraordinary rewards on the side of Allah SWT. In a marriage, it is required to carry out several terms and conditions that have been widely explained in the Al-Quran and hadiths, one of which is the condition and obligation for the validity of marriage is the presence of the guardian (father and brother from the father's side) of the bride. The presence of this guardian in marriage is mandatory and if his presence cannot be done or the guardian is reluctant to attend his child's marriage then the guardian is included in the category of wali adhal. This study uses a research method by analyzing the decision on the marriage case of wali adhal in the marriage of a girl in the Bogor Religious Court, the method used is literature. The results of the decision the judges granted by listing several reasons, one of the reasons is because they already love each other and love each other and have been together for a long time, so the application for marriage is granted while the biological guardian is reluctant to allow her marriage to the prospective husband of her choice, so it is replaced by a guardian judge who is directly appointed by the head of the panel of judges at the Bogor Religious Court, namely the Head of the Religious Affairs Office of East Bogor District, Bogor City asa guardian judge who will marry the applicant with the prospective husband.